Effect of Sub-Lethal Concentration of Iron on Growth and Survival of Daphnia (Müller, 1785) - Kumar, Kanchan; Tiwari, V. K.; Dube, Kiran; Prakash, Chandra; Babitha Rani, A. M.; Verma, A. K. (Fishery Technology, 2020)
In the present study the effect of iron on growth and survival of Daphnia (Müller, 1785) has been studied. Neonates of Daphnia were exposed to different water-borne iron concentrations. Although iron is toxic at high concentrations, they are also essential elements required for many biological processes. Iron is a vital metal for Daphnia for normal development and reproduction. Mass culture of Daphnia has been done in plastic tubs. During experiment, the effects of iron on Daphnia were studied at an exposure equivalent to the 48 h LC50. Based on the LC50, seven Fe2+ levels (prepared through serial dilution from a stock solution of 5 mgL-1) for the chronic toxicity tests were selected. These were 0, 0.25, 0.50, 1.00, 2.00, 4.00 and 8.00 mg L-1of Fe2+. The population density of Daphnia increased with increase of sub-lethal dosages of iron and decreased significantly at higher toxic dosages, indicating that iron is required as micronutrients for stimulating growth in terms of population density.